2021
DOI: 10.15252/embr.202052061
|View full text |Cite
|
Sign up to set email alerts
|

Non‐redundant functions of H2A.Z.1 and H2A.Z.2 in chromosome segregation and cell cycle progression

Abstract: H2A.Z is a H2A-type histone variant essential for many aspects of cell biology, ranging from gene expression to genome stability. From deuterostomes, H2A.Z evolved into two paralogues, H2A.Z.1 and H2A.Z.2, that differ by only three amino acids and are encoded by different genes (H2AFZ and H2AFV, respectively). Despite the importance of this histone variant in development and cellular homeostasis, very little is known about the individual functions of each paralogue in mammals. Here, we have investigated the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…In prostate cancer, H2A.Z.1 appears to regulate androgen-dependent cell proliferation [47], while the isoform H2A.Z.2 is required for cellular proliferation in metastatic melanoma [48]. A recent study has also reported differential functions in chromosome segregation and cell cycle progression, where H2A.Z.1 regulates the expression of key cell cycle genes such as Myc in human cells, while H2A.Z.2 is essential for centromere function and the regulation of sister chromatic cohesion [51]. Interestingly, the expression of H2A.Z.1 correlated with MYCN amplification in neuroblastoma patients and survival analysis showed patients with higher H2A.Z.1 levels have worse prognosis [51].…”
Section: H2az Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…In prostate cancer, H2A.Z.1 appears to regulate androgen-dependent cell proliferation [47], while the isoform H2A.Z.2 is required for cellular proliferation in metastatic melanoma [48]. A recent study has also reported differential functions in chromosome segregation and cell cycle progression, where H2A.Z.1 regulates the expression of key cell cycle genes such as Myc in human cells, while H2A.Z.2 is essential for centromere function and the regulation of sister chromatic cohesion [51]. Interestingly, the expression of H2A.Z.1 correlated with MYCN amplification in neuroblastoma patients and survival analysis showed patients with higher H2A.Z.1 levels have worse prognosis [51].…”
Section: H2az Isoformsmentioning
confidence: 99%
“…(C) EP400 knockout in Schwann cells (SC) causes abnormal maturation, myelin defects, and neuropathy through a process that involves aberrant upregulation of the Schwann cell progenitor (SCP) marker Tfap2a at later stages during SC maturation. See also [49][50][51]105]. to decreased H2A.Zac levels, but not total H2A.Z, and diminished RNAPII pausing [46].…”
Section: Open Accessmentioning
confidence: 99%
“…iHCC mimics the histological architecture, tumor serum marker profile, and gene expression characteristics of human HCC. However, Ki‐67, a marker of proliferation (Sales‐Gil et al , 2021), was highly expressed in iHCC, which is not common in primary human HCC, possibly indicating the aggressiveness of iHCC. To our knowledge, it is the first in vivo model of orthotopic transformation of human PHHs into HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Histone H2A.Z increases enhancer activity, facilitating the binding of transcription factors and chromatin remodelers to trigger transcription and changes in the 3D chromatin structure [ 129 ]. H2A.Z histone also plays an important role in chromosome segregation and cell cycle progression, whereby H2A.Z upregulates the expression of key cell cycle genes, such as c-Myc, Myc-N, KIi67, and AURKA [ 130 ]. In addition, H2A.Z fine tunes processes of cell renewal and mediates the establishment of bivalent promoters of developmental genes during embryonic stem cell differentiation [ 131 ].…”
Section: Myc and Polyploidy Open Chromatin At The Low Level Of Organi...mentioning
confidence: 99%
“…In addition, H2A.Z fine tunes processes of cell renewal and mediates the establishment of bivalent promoters of developmental genes during embryonic stem cell differentiation [ 131 ]. The reduction in H2A.Z in mESCs results in loss of pluripotency, premature differentiation, and senescence [ 130 ]. Another important Myc partner implicated in chromatin opening is WDR5, which facilitates histone H3 Lys4 (H3K4) methylation and increases the affinity of MYC for active promoters [ 65 ].…”
Section: Myc and Polyploidy Open Chromatin At The Low Level Of Organi...mentioning
confidence: 99%